Gait and Functional Mobility in Multiple Sclerosis: Immediate Effects of Transcranial Direct Current Stimulation (tDCS) Paired With Aerobic Exercise - Pilloni, Giuseppina; Choi, Claire; Coghe, Giancarlo; Cocco, Eleonora; Krupp, Lauren B.; Pau, Massimiliano; Charvet, Leigh E. (Frontiers in Neurology, 2020)
Walking impairments are a debilitating feature of multiple sclerosis (MS) because of the direct interference with daily activity. The management of motor symptoms in those with MS remains a therapeutic challenge. Transcranial direct current stimulation (tDCS) is type of non-invasive brain stimulation that is emerging as a promising rehabilitative tool but requires further characterization to determine its optimal therapeutic use. In this randomized, sham-controlled proof-of-concept study, we tested the immediate effects of a single tDCS session on walking and functional mobility in those with MS. Seventeen participants with MS completed one 20 minute session of aerobic exercise, assigned to be paired with either active (2.5 mA, n=9) or sham (n=8) tDCS over the primary motor (M1) cortex. The groups were matched according to gender (50% vs 60% F), age (52.1 ± 12.85 vs 54.2 ± 8.5 years), and level of neurological disability (median EDSS: 5.5 vs 5). Gait speed on the 10-meter walk test and the Timed Up and Go (TUG) time were measured by an inertial sensor before and following the 20 minute session, with changes compared between conditions and time. There were no significant differences in change in gait speed or TUG time following the session in the full sample or between active vs. sham groups. These findings suggest that a single session of tDCS over M1 is not sufficient to affect motor functions in those with MS. Instead, motor response of tDCS is likely to be cumulative and the effects of multiple tDCS sessions requires further study.